Erythrocyte transfusions increased the risk of elevated serum ferritin in very low birthweight infants and were associated with altered longitudinal growth - Alm, Stina (Acta Paediatr, 2020)
AIM: There has been a lack of population‐based longitudinal data on serum ferritin in very low birthweight (VLBW) infants during hospitalisation. Our aim was to fill this gap in the knowledge and investigate risk factors for elevated serum ferritin and associations between erythrocyte transfusions and longitudinal growth. METHODS: We retrospectively reviewed longitudinal data on 126 VLBW infants treated at Umeå University Hospital, Sweden, between 2010 and 2013. RESULTS: The infants' mean gestational age and birthweight were 26.9 weeks and 899 g. Most (91%) received erythrocyte transfusions, and the majority had multiple erythrocyte transfusions. There was a significant correlation between serum ferritin and the volume of transfusions. Almost two‐thirds had at least one serum ferritin measurement of more than 350 µg/L, indicating iron overload. In those with complete anthropometric data (n = 78), there was no significant effect of serum ferritin concentrations in relation to longitudinal growth, but there was a positive association between the erythrocyte transfusion dose and longitudinal growth in VLBW infants born before 25 weeks. CONCLUSION: This is the first population‐based study to investigate longitudinal data on serum ferritin in VLBW infants during hospitalisation. The unexpected positive finding in the subgroup born at less than 25 weeks needs further research with a larger cohort.